Defining the ethical standards of the high-technology industry. - Fimbel, Nancie; Burstein, Jerome S. (Journal of Business Ethics, 1990)
Employees in high tech industries are no more ethically lax than are those in other industries, according to the results of a recent survey. A questionnaire asking employees to rate the workplace acceptability of ethical behaviors relating to safety, third parties, and cheating the company was sent to 89 members of the Association for System Management, whose members are systems analysts, computer programmers, and information systems consultants. The mailing yielded 36 usable responses. The control sample consisted of 39 randomly selected people in San Jose, Charlotte, and suburban Boston who returned usable questionnaires. While the sample is admittedly small, the results indicate that high tech employees are unwilling to violate general cultural values of safety or to treat third parties unethically, they disapprove of more ethically questionable behaviors than does the general public, and they disapprove more strongly than do randomly selected workers.